P55 Train the trainers in situ: a fresh take on an established course. (November 2018) - Websdale, Daniel; Wright, David; Blackmore, Andrew; Major, Donna; Purva, Makani; Gay, Christopher
Abstract : Introduction: The Train the Trainers course is one well known to those involved in simulation. However learning techniques are changing and with the increasing difficulty of obtaining study leave for full day courses brought the emergence of training within the clinical environment without the use of real patients. Therefore the HILS team created a one day course to bring together the essential knowledge and skills needed for delivering in situ simulation training. The course has currently ran twice and taught eleven candidates of varying professions. Method: The course is broken down into short sessions lasting approximately one hour, they cover: Introduction to simulation and in situ simulation Technical considerations – equipment demonstration e.g. cameras/video replay Safety considerations – latent errors and videos in clinical areas Planning of in situ scenario – learning outcomes and audience Debriefing. Once all sessions are complete, Sim Man 3G and in situ equipment is prepared and transported to the Emergency Department (ED) on site to an area that is free from live patient interaction. When ED is unavailable due to over crowdedness, the HILS team recreates the in situ environment by running the scenario in either their sluice room or small communication room to increase the realism. A scenario debrief concludes the course. Pre and post-course questionnaires using a 7-point Likert scale were completed by all candidates to measure confidence levels of three areas: Identifying the technical and safety considerations for in situ simulations Delivering in situ simulations Delivering debriefs for in situ simulations. Results: The pre/post mean score for the three questions explored are shown in the table 1 below: 'Not using ED did not cause much change to the outcome' Conclusion and recommendations: The mean scores for all three questions showed improvement which shows an increase in knowledge and confidence in the areas measured. However to determine the full extent of the confidence increase, the measurement should be taken after their first live in situ to gain a true reflection; however logistical implications of this are recognised. It could be beneficial to make prior arrangements with other departments to run the scenario there if the ED department becomes unavailable at short notice, but as one candidate stated, it had a low impact on the outcome. The course is planned to run again at the end of this year. References: http://www.heyhils.co.uk/courses/train-the-trainer-in-situ-course